The Path to Democracy? Foreign Aid Post-Military Coup in Myanmar (Global Focus, 2021)
Aid has transformed into a promising tool of policy to spread, gain, or maintain power and influence internationally. One of the common aid institutions keeps actively promoting and pushing norms and values of democracy internationally in the United States through USAID. Upon that, one of the recipient countries to receive USAID programs in Myanmar. USAID has been focusing on and pushing democratization to occur in Myanmar and creating supporting programs to respond to the 2015 election, increasing the number of aids after the majority win of the NLD Party in the 2015 election. However, after the military coup successfully seized the government on February 1, 2021, USAID decided to shift its programs to support the civil society movement and strengthen democracy in Myanmar. Within this paper, there will be explanations of how USAID's programs after the military coup occurred in Myanmar, and why it matters to the United States not fully to halt their programs and aids of USAID. This paper will also show how USAID programs and aid to Myanmar before the coup.